2017
DOI: 10.2514/1.c034057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Vortical Flow on Swept Wings with Round Leading Edges

Abstract: The present work is investigating the vortex-dominated flow physics as well as the aerodynamic behavior of swept wing configurations with round leading edges. The research is based on numerical simulations using the computational fluid dynamics method DLR TAU. The target configurations are swept wings of constant aspect ratio, variable leading-edge contours, and leading-edge sweep angles. The work deals with the onset of the vortical flow at the leading edge for constant and variable leading-edge nose radii, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…In addition, these complex flow structures over moderately swept wings are still a challenge for computer simulations (7)(8)(9)(10)(11)(12)(13)(14) . For example, Li and Leschziner (7,8) used the large eddy simulation (LES) and a wall function approach to simulate the highly complex separated flow over a swept wing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these complex flow structures over moderately swept wings are still a challenge for computer simulations (7)(8)(9)(10)(11)(12)(13)(14) . For example, Li and Leschziner (7,8) used the large eddy simulation (LES) and a wall function approach to simulate the highly complex separated flow over a swept wing.…”
Section: Introductionmentioning
confidence: 99%
“…Theories for FEM are summarized, among others, in MSCNastran's Getting Started Guide [14]. Preliminary design [8] and the latest aerodynamic investigation [7] are providing the basic shape (layout and airfoils). Positions and sizes of system items are defined as well.…”
Section: Structural Modelmentioning
confidence: 99%
“…Aerodynamic integration matrix (7) c p = AIC(Ma, k) ⋅ w j contains several sources of aerodynamic forces. Forces due to rigid body motions are given by D jrbm u rbm and control surface deflections are considered in D jcs u cs .…”
Section: Aerodynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in higher lift and lower drag coefficients. Schütte conducted an extensive numerical investigation of the flow field sensitivity to the change in leading-edge sweep ϕ, angle of attack α, Mach number Ma and leading-edge radius r le [13]. He demonstrated that the separation onset moves upstream with decreasing r le and ϕ, on one hand, and with increasing α and Ma, on the other.…”
Section: Introductionmentioning
confidence: 99%